On Using Negative Binomial Distribution as a Randomization Device in Sensitive Surveys. Issue 10 (25th November 2016) - Hussain, Zawar; Al-Zahrani, Bander; Shabbir, Javid; Khan, Manzoor
Abstract : In this article, an interesting improvement of some recent randomized response techniques has been proposed. The proposed randomized response technique applies Negative Binomial distribution to obtain data from respondents. An unbiased estimator of proportion of a sensitive attribute has been suggested and it is shown, numerically, that the new estimator performs better than the recent estimators while doing a sensitive survey. It is also established that the proposed estimator is unconditionally better than that of the estimator based on using the geometric distribution.